Implementation of Guided Discovery Learning to Improve Chemistry Learning Outcomes in Hydrocarbon Topics of Students' at SMK Negeri 2 Palembang - Putri Apriogansi; Muhammad Hadeli; Meidia Farlina (Pedagogy Review, 2022)
Abstract: The aim of this classroom action research is to improve chemistry learning outcomes of student in class X Geomatika 2 SMK Negeri 2 Palembang by implementation of guided discovery learning model. Research conducted at SMK Negeri 2 Palembang with the subject of the research are 34 students of class X Geomatika 2 consist of 21 men and 13 women. The acts of research are consists of two cycles, each cycle performes two meetings. Data collection is done with test in ending of cycle and observation through the learning proccess. The average student learning outcomes in pre-cycle (T0) are 72,35 with percentage of mastery learning are 67.65%. Based on the results of the research, average score in first cycle (T1) are 79.81 with percentage of mastery learning are 79.41%. In second cycle (T2), average score are 84,85 with percentage of mastery learning are 88.24%. Results of this research by using guided discovery learning model increase the learning outcomes of students in the subjects of chemistry shown from T2 higher than T1 higher than T0. Keywords: learning model, guided discovery, student chemistry learning outcomes.